Hsa_circ_0000437 Inhibits the Development of Endometrial Carcinoma through miR-626/CDKN1B Axis - Li, Xiaojuan; Liu, Yahong (Protein and Peptide Letters, 2022)
Background: Circular RNAs (circRNAs) are pivotal in cancer biology. Nevertheless, the biological functions of circular RNA hsa_circ_0000437 (circ_0000437) have not yet been elucidated. In the present study, we studied the expression characteristics of circ_0000437 in endometrial carcinoma (EC) and explored the roles and potential mechanisms of circ_0000437 in EC progression. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was adopted to detect the expressions of circ_0000437, microRNA-626 (miR-626) and cyclin-dependent kinase inhibitor 1B (CDKN1B) in EC tissues and cells. 5-Ethynyl-2'-deoxyuridine (EdU), cell counting kit-8 (CCK-8) and Transwell assays were performed to evaluate EC cell proliferation and invasion. The expressions of CDKN1B and epithelial-mesenchymal transition (EMT)-related proteins (E-cadherin and N-cadherin) were detected by Western blot. Moreover, the targeted relationship between miR- 626 and circ_0000437 or CDKN1B was determined by a dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. Results: Circ_0000437 expression was reduced in EC tissues, and the low expression of circ_0000437 was positively correlated with the lymph node metastasis and high TNM stage of EC patients. Knocking down circ_0000437 promoted the proliferation, invasion and EMT of EC cells. Circ_0000437 directly targeted miR-626 and negatively modulated miR-626 expression in EC cells. CDKN1B was identified as the downstream target of miR-626 in EC cells. Besides, CDKN1B overexpression of miR-626 knockdown reversed the effects of knocking down circ_0000437 on EC cells. Conclusion: Circ_0000437 regulates the miR-626/CDKN1B pathway to suppress the proliferation, invasion and EMT of EC cells. This indicates that circ_0000437 may be a promising biomarker and therapy target for EC.
Keywords: CDKN1B